Sikakap Bercadar : Pola Internalisasi di Kalangan Perempuan Desa Sikakap Kepulauan Mentawai - Ummi Kalsum; Darmaiza Darmaiza; Dwi Wahyuni (Universitas Islam Negeri Imam Bonjol Padang, 2021)
The spread of the veil in da’wah program of Tablighi has implications for the use of the veil among women in Sikakap Village, Mentawai Islands. Raising several questions such as how does the veil spread?; and what is the pattern of internalization of the veil that is instilled by the Tablighi? This research was conducted by direct observation and interviews with 9 informants equipped with documentation data. Then the data was analyzed using Miles and Huberman’s interactive analysis which includes three things, namely reduction data, presentation data, and conclusions. This study found that Taklim Masturoh became a media used by Tablighi in distributing the veil in Sikakap Village, Mentawai Islands. The pattern of internalizing the veil in Sikakap Village is carried out in the Taklim Masturoh activity with four stages, first, introducing oneself and religion called ta’aruf. Second, ta’allub, connecting with new members by explaining that fellow Muslims are brothers, the purpose of being brothers is so that one another has the right to remind one another, save one another and pray for one another. Third, targhib, adding motivation and support to taklim members or giving encouragement in carrying out Allah’s command and all things that Allah has forbidden. Fourth, tasyki, invite members slowly.